(2*4.6*9+4*9.2*18/1*2.3*4.5+3*6.9*13.5)=?急
3个回答
(2*4.6*9+4*9.2*18)/(1*2.3*4.5+3*6.9*13.5)
=[1*2.3*4.5*(2+4)]/[1*2.3*4.5*(1+3)]
=(2+4)/(1+3)
=1.5
相关问题
(1)4、9、9、12(2)3、7、9、13(3)1、2、4、6(4)2、8、9、13(5)1、6、6、8(6)2、3、
1/3+2/3+1/6+2/6+3/6+4/6+5/6+1/9+2/9+3/9+4/9+5/9+6/9+7/9+8/9+
6-2 3 5 = 18 9 13 ÷9= 5.6× 4 7 = 1 3 + 1 6 = 8÷ 4 7 = 4 5 ÷0
1乘2.3乘4.5加3乘6.9乘13.5分之2乘4.6乘9加4乘9.2乘18是多少?
1 5 5 5 3 7 9 13 2 6 9 9 5 5 10 13 2 4 10 10
数字推理 2 3 1 4 9数字推理 2 ,3 ,1 ,4 ,9,1,2,4,3,5,6,9,18?0,2,1,3,4,
(5/9+1/36)*9+3/4 (5/12+1/6)/(2/5*7/8) 7.6/13+5.4*1/13 5/6/{(
将1/2 1/3 1/6 1/9 2/9 4/9 5/9 5/18 7/8
6 7 9 16 4 3 2 4 6 11 5 32 18 10 13
口算:18÷9×5= 4.8+10.2= 6-2.5= 9.6-3.6= 17.9-4.5= 7.3+2.61= 50×